(untitled) (Fiep Bulletin - online, 2012)
The aim of this study was to deepen the knowledge on the death theme, hardly ever studied, especially inSports Sciences. The objectives established were to analyse the death concept among the elderly citizens in anactive and in a sedentary group; to compare the speech on death between the seniors from both groups and tounderstand how their active/sedentary life-styles influence their death concept. Six categories were established:anguish towards death; death as taboo; death as the end; death as a consequence of life; the relationship betweenold age and death/ the relationship between the being and death.It was observed that the death theme brings about contradictory feelings, regardless of one’s lifestyle. Itwas clear that sedentary seniors were more deeply anguished about death. They accept it more pacifically as well asthe process that may lead to death, even when there is much suffering. The active elderly are more expressive intheir answers, producing a more positive speech on the theme. Choosing an active lifestyle marked by dynamism,socialization, new and different appeals is an attitude towards life and death that offers people, especially the aged,a more expressive, more positive and more dignifying existence.